2016
DOI: 10.1038/srep33444
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) ions affect the gating dynamics of the 20S proteasome: a molecular and in cell study

Abstract: Due to their altered metabolism cancer cells are more sensitive to proteasome inhibition or changes of copper levels than normal cells. Thus, the development of copper complexes endowed with proteasome inhibition features has emerged as a promising anticancer strategy. However, limited information is available about the exact mechanism by which copper inhibits proteasome. Here we show that Cu(II) ions simultaneously inhibit the three peptidase activities of isolated 20S proteasomes with potencies (IC50) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 46 publications
4
21
0
Order By: Relevance
“…Proteasome agonists may act through two different main mechanisms namely, i) the promotion of substrate entry into the catalytic chamber by inducing opening of the α‐ring gate (gate openers), ii) stimulation of substrate binding to the catalytic pockets and degradation induced by allosteric interactions. In order to confirm whether pyrazolones may activate proteasome by inducing gate opening of the α‐ring, we assayed the effect of aminopyrine on the ChT−L activity of a mutant yeast 20S proteasome (α3ΔN) which lies in a permanently open gate conformation (Figure and Figure S1B of Supporting Information) . Aminopyrine, differently from the WT yCP, does not activate the α3ΔN mutant, consistent with the hypothesis that the ligand influences the gating mechanism without any effect on the allosteric activation of the catalytic sites.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Proteasome agonists may act through two different main mechanisms namely, i) the promotion of substrate entry into the catalytic chamber by inducing opening of the α‐ring gate (gate openers), ii) stimulation of substrate binding to the catalytic pockets and degradation induced by allosteric interactions. In order to confirm whether pyrazolones may activate proteasome by inducing gate opening of the α‐ring, we assayed the effect of aminopyrine on the ChT−L activity of a mutant yeast 20S proteasome (α3ΔN) which lies in a permanently open gate conformation (Figure and Figure S1B of Supporting Information) . Aminopyrine, differently from the WT yCP, does not activate the α3ΔN mutant, consistent with the hypothesis that the ligand influences the gating mechanism without any effect on the allosteric activation of the catalytic sites.…”
Section: Resultssupporting
confidence: 65%
“…The 20S proteasome is made up by 28 subunits arranged in four stacked heptameric rings (α1–7, β1–7, β1–7, α1–7), with a symmetric, cylinder shaped, heterodimeric structure containing three couples of catalytic β subunits (β5, β2 and β1) exhibiting chymotrypsin‐like (ChT−L), trypsin‐like (T−L), and peptidylglutamyl peptide hydrolyzing (PGPH) activity, respectively . The 20S external α‐rings form a narrow gate that regulates substrate access into the inner catalytic chamber and may interact with one (26S), or two (30S) 19S regulatory particles . The 26S proteasome mainly targets structured proteins thanks to the assistance of 19S RPs which recognize and unfold polyubiquitinated protein substrates .…”
Section: Introductionmentioning
confidence: 99%
“…The noncatalytic inhibition of the proteasome by USP14 is mediated by the direct interaction with the ATPase ring of the proteasome; this process results in strong interference with RPN11 function and with a conformational change of the proteasome for proper substrate translocation [16]. USP14 is also involved in the “gating” system which is controlled by various cellular factors including metal ions [17-19]. Therefore, mammalian proteasomes function under tonic inhibition by USP14, which expected to be crucial as a secondary quality control mechanism for intracellular proteins.…”
Section: Introductionmentioning
confidence: 99%
“…They found that although ubiquitine dependent proteolysis was inhibited by copper complexes in a concentration-dependent manner, a moderate recovery of proteasome activity in HeLa cells at 80 μmol/L compared to samples exposed to a concentration of 40 μmol/L was observed. The authors ex- plain this effect by the increased presence of ROS in HeLa cells (at higher copper concentration) and subsequent activation of the antioxidant defense of the cell, which activates inhibited proteasome (23). This fact indicates that HeLa cells are less sensitive to the proteasome inhibition by copper complexes.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the fact that we found no ubiquitin bands after the treatment of HeLa and U-118MG cells with our copper complexes, we cannot clearly state whether our tested copper complexes are/are not proteasome inhibitors in those cells. The proteasome inhibitory action of different copper complexes in HeLa cells was observed by Santoro et al (2016). They found that although ubiquitine dependent proteolysis was inhibited by copper complexes in a concentration-dependent manner, a moderate recovery of proteasome activity in HeLa cells at 80 μmol/L compared to samples exposed to a concentration of 40 μmol/L was observed.…”
Section: Discussionmentioning
confidence: 99%